Methodical preparation as a means of developing prospective mathematics teachers' ICT competency - Iryna Lovianova; Andriy Krasnoschok; Ruslan Kaluhin; Olena Kozhukhar; Denys Dmytriyev (Academy of Cognitive and Natural Sciences, 2021)
The purpose of the study is modeling of ICT competence formation of would-be mathematics teachers through the best practice application of effective ICT tools. The objectives of the study are to analyze the possibilities of creating conditions for the formation of competent mathematics teachers using ICT tools. The object of the study is the methodical preparation of students of pedagogical HEIs by means of ICT. The subject of study is the peculiarities of the formation of a competent mathematics teacher in classes on methodological disciplines. The authors of the article analyze, summarize and systematize research on the issue of using ICT tools in the training students' activities in Universities of Teacher Education. The study determines the role of methodological training in the development of ICT competence of would-be mathematics teachers. The authors of the study developed a model for building competence would-be mathematics teachers, which consists of four components. There is the target, preparatory, procedural, and resulting constituents. The model describes a systematic approach to the organization of students' training activities in the in teaching the disciplines of professional and practical training. Giving an account of the integration nature of the methodological students' training, it also considers the organization of distance communication between students and teachers. This paper presents examples of the implementation of the components of the model. The examples describe the implementation by students of course projects and degree projects on teaching mathematics methodologies using ICT tools. A pedagogical experiment was conducted to evaluate the effectiveness of ICT tools in the training of would-be mathematics teachers. The results of the study confirmed the effectiveness of modeling the organization of students' activities to develop their ICT competency. As the follow-up research directions, we consider summarizing recommendations on the usage of ICT in the preparation of competent socionomic specialists.